2019
DOI: 10.21203/rs.2.17989/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Validation of RESP and PRESERVE score for ARDS patients with pumpless Extracorporeal Lung Assist (pECLA)

Abstract: Background: RESP score and PRESERVE score have been validated for veno-venous Extracorporeal Membrane Oxygenation in severe ARDS to assume individual mortality risk. ARDS patients with low-flow Extracorporeal Carbon Dioxide Removal, especially pumpless Extracorporeal Lung Assist, have also a high mortality rate, but there are no validated specific or general outcome scores. Methods: In a retrospective single center cohort study we calculated and evaluated RESP, PRESERVE, and SOFA score for 73 ARDS patients wit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…54 articles were retrieved for full-text review, 21 of which were finally included in the systematic review and meta-analysis. These included three randomised controlled trials [8,17,18], totalling 531 patients, and 18 observational studies [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36], ranging from non-randomised controlled designs to retrospective cohort studies. Most studies were published in the past decade (n=15, 71%) [8,18,[24][25][26][27][28][29][30][31][32][33][34][35][36] and evaluated veno-venous ECCO 2 R (n=12, 57%) [8, 17, 19, 21, 27, 29-33, 35, 36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…54 articles were retrieved for full-text review, 21 of which were finally included in the systematic review and meta-analysis. These included three randomised controlled trials [8,17,18], totalling 531 patients, and 18 observational studies [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36], ranging from non-randomised controlled designs to retrospective cohort studies. Most studies were published in the past decade (n=15, 71%) [8,18,[24][25][26][27][28][29][30][31][32][33][34][35][36] and evaluated veno-venous ECCO 2 R (n=12, 57%) [8, 17, 19, 21, 27, 29-33, 35, 36].…”
Section: Resultsmentioning
confidence: 99%
“…For observational studies, 12 studies reported a mortality outcome (five hospital mortality [18,19,22,24,34], two 28-day mortality [29,36], three both hospital and 28-day mortality [23,28,31] and two ICU mortality [25,27]). Among studies including >50 patients, reported mortality ranged from 37.9% to 58.9% [20,22,28,30,31,34].…”
Section: Mortality Ventilator-free Days and Length Of Staymentioning
confidence: 99%